Efektifitas Kombinasi Model Pembelajaran Berbasis Masalah dan Model Hybrid Learning untuk Meningkatkan Keterampilan Pemecahan Masalah - Zainudin; Didik Hermanto; Rica Wijayanti; Hunaepi (Postgraduate, University of Mataram, 2023)
The research objective is to describe the effectiveness of the combination of the PBL (Problem-Based Learning) model and hybrid learning in improving problem-solving skills.. This research is a quasi-experimental design with a non-equivalent control group design. The research subjects were 40 students consisting of an experimental class and a control class in the fourth semester of the PGSD STKIP PGRI Bangkalan study program. The results showed that the N-Gain values for the experimental class and the control class were .89 and 1.43. The hypothesis test using SPSS shows that the Sig (2- tailed ) value in the experimental class is .000 <0.05 with a t-count value of 6.389 <t-table 0.687, that is to say there is a significant difference, the combination of the PBL model and the hybrid learning model and the learning model direct. Based on the results of data analysis, it can be concluded that the combination of the PBL model and the hybrid learning model is effective in improving problem solving skills.